O GOSTO PELO CANTO CORAL PROTESTANTE NO BRASIL: HISTÓRIAS E TENSÕES EM UM CAMPO MUSICAL - Vieira, Carlos Eduardo da Silva (2012)
The dissertation elaborates reflexive considerations about choir singing as a cultural social practice in Brazilian Protestantism. The text directs its attention towards choir singing and its idiosyncrasies using the bases of Pierre Bourdieu's sociology and its application to sociological discussions on taste as a social reality defined by tensions created in the cultural milieu to which the concepts field, habitus and capital apply. Choir singing as a cultural practice is presented and a historic is traced since its origins until actual days. Focus falls upon uses of choir singing for the most different varieties of Protestantism in order to track the aspects that revealed themselves preponderant when this cultural practice arrived in Brazil and also to understand facts and characters that made Brazilian evangelical choir singing take the historical routes that brought it to occupy a place of high cultural value in Brazilian protestant culture. Later, commotions to the choir singing caused by social changes that deeply re-characterized musical taste in the Protestantism of that country are verified. The discussion follows to an analysis of the fights that those new configurations are establishing inside religious field and to the expressions of these battles in a market of symbolic goods that comprehends and orients them. With the goal of determine the subjects involved, the main adversaries of choir singing in Brazilian evangelic field are presented and, finally, three projects that, in the last decades, have reached impact in the protestant midst as defenders of choir singing are delineated.